2017
DOI: 10.1021/acs.jctc.7b00302
|View full text |Cite
|
Sign up to set email alerts
|

Singlet La and Lb Bands for N-Acenes (N = 2–7): A CASSCF/CASPT2 Study

Abstract: In this work CASPT2 calculations of polyacenes (from naphthalene to heptacene) were performed to find a methodology suitable for calculations of the absorption spectra, in particular of the L (B state) and L (B state) bands, of more extended systems. The effect of the extension of the active space and of freezing σ orbitals was investigated. The MCSCF excitation energy of the B state is not sensitive to the size of the active space used. However, the CASPT2 results depend strongly on the amount of σ orbitals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 72 publications
(163 reference statements)
5
36
0
Order By: Relevance
“…The concept of a structure related topological phase transition and the corresponding bandgap closure is exemplified in Fig 1A for the structure family of ethynylene-bridged polyacene polymers. Both DFT and tight-binding calculations shows a monotonic decrease of the HOMO-LUMO gap of the polyacene monomer as a function of the acene size (where n denotes the number of benzene rings of the polyacene) (24) (see also Fig. S1), as expected from the increasing delocalization of the frontier orbitals.…”
Section: Main Textmentioning
confidence: 68%
“…The concept of a structure related topological phase transition and the corresponding bandgap closure is exemplified in Fig 1A for the structure family of ethynylene-bridged polyacene polymers. Both DFT and tight-binding calculations shows a monotonic decrease of the HOMO-LUMO gap of the polyacene monomer as a function of the acene size (where n denotes the number of benzene rings of the polyacene) (24) (see also Fig. S1), as expected from the increasing delocalization of the frontier orbitals.…”
Section: Main Textmentioning
confidence: 68%
“…949 A recent CASPT2 study investigated the different computational requirements for describing the La and Lb states of polyacenes. 952 As opposed to the MR studies, which showed rather uniform trends for the excitation energies, a DFT study presented some evidence suggesting that the optical gaps oscillate with increasing size of the oligoacene. 953 Finally, a recent CASPT2 study 540 In addition to polyacenes, a wide range of other PAHs have been studied by multireference methods.…”
Section: Polycyclic Aromatic Systems: Monomers and Dimersmentioning
confidence: 88%
“…The latter geometries were very similar to def2-SVP optimized ones ( Regarding the monomer (TABLE V), DFT/MRCI predicts excitation energies of 2.69 and 3.27 eV for 1 1 B2u and 1 1 B3u states, in excellent agreement with experimental results 87,88 and previously reported calculations with DFT/MRCI, 85 using both SV(P) and TZVP basis sets, and CASPT2. 86 Other methods predict higher excitation energies for both states and a varying energy gap between them, such as 0. There is an overall good agreement among dimer spectra using different methods (FIG.…”
Section: B Dimer Vertical Excitations At Optimized Geometriesmentioning
confidence: 99%